CARICATURE AS A METHOD OF CREATING CHOREOGRAPHY - Vladova, Silvina (E-Journal VFU, 2025)
In this paper an attempt will be made to present the possibilities of using caricature as a method of creating choreography. The proposed paper analyses the artistic caricature and how it provokes the creation of a narrative dance or dance étude. It will present possible techniques for developing a dance étude with appropriate dance vocabulary, stylistic and artistic devices. How to caricature art contributes to the development of the dance form will be sought and highlighted. The research is based on the study process with students at Southwest University "Neofit Rilski" in the Department of Choreography, 223 majoring in Contemporary Choreography. And the results show that caricature as an artistic expression not only enriches the dance form but also provokes fruitful activity on the part of students, leading to new interpretations and depth of perception. An intersection and emotional compatibility are sought in the expression of dance and caricature, which in itself leads to another type of relevance and new perspectives in the use of dance as a vehicle for social connectivity, emotional expression and dance therapy, where the caricature element can provide an accessible way to overcome psychological barriers.